Effects of organic fertilizers on yield, soil physico-chemical property, soil microbial community diversity and structure of Brassica rapa var. Chinensis - Zhang, Xia; Li, Jian; Shao, Le; Qin, Feng; Yang, Jie; Gu, Hongru; Zhai, Pin; Pan, Xiaoqing (Frontiers in Microbiology, 2023)
The amount of chemical fertilizer for vegetables is on the high level in China. The use of organic fertilizers to meet the nutrient requirement of crops will be an inevitable practice in sustainable agriculture. In this study, we compared the effects of pig manure fertilizer, rabbit manure fertilizer and chemical fertilizer on yield, quality of Brassica rapa subsp. Chinensis, soil physico-chemical properties and microbial community by using two consecutive seasons of three fertilizers in a pot experiment. The results were as follows: (1) In the first season, the fresh yield of Brassica rapa subsp. Chinensis applying chemical fertilizer was significantly (P ≤ 5 %) higher than those of applying the pig manure and rabbit manure fertilizer, and the results were the opposite in the second season. The total soluble sugar concentration of fresh Brassica rapa subsp. Chinensis applying rabbit manure fertilizer was significantly (P ≤ 5 %) higher than those of applying pig manure fertilizer and chemical fertilizer in the first season, and the NO3-N content of fresh Brassica rapa subsp. Chinensis on the contrary. (2) The organic fertilizer increased the concentration of total nitrogen, total phosphorus and organic matter in soil in both two seasons. Rabbit manure fertilizer increased the soil pH and EC and significantly (P ≤ 5 %) reduced the soil NO3-N content. (3) The pig manure and rabbit manure fertilizer significantly (P ≤ 5 %) increased the diversity and abundance of soil bacterial of Brassica rapa subsp. Chinensis, but had no significant effect on soil fungi. Pearson correlation analysis showed that soil TN, TP, organic matter content and EC were significantly correlated with soil bacterial α - diversity. There were significant differences (P ≤ 5 %) in the bacterial community structures between three treatments in two seasons, and significant differences (P ≤ 5 %) in the fungal community structures between fertilizer treatments while not between two seasons. Pig manure and rabbit manure fertilizer decreased the relative abundance of soil Acidobacteria and Crenarchaeota, rabbit manure fertilizer significantly increased the abundance of Actinobacteria in the second season.